Право в естетичному вимірі (до постановки питання) - Бурлай, Є.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2004)
Статья посвящена проблемам соотношения права и эстетики как специфических способов социально-нормативного регулирования в человеческом обществе, возможности изучения права в целом
и отдельных явлений в правовой сфере в эстетическом аспекте. Подчеркивается, что меры эстетического плана могут повышать эффективность правового регулирования, поскольку эстетика обладает сильными (хотя скрытыми и недостаточно изученными) возможностями влиять на поведение людей. The article is dedicated to problems of correlation of law and aesthetic as specific types of social normative
regulation in a human society; to possibilities of studying the law as a whole and some phenomena of
aesthetical nature in the sphere of law. The author accents the point that some means of aesthetical influence
can effectively increase the effectiveness of the legal regulation because of its latent but still strong and not learned enough possibilities to affect human behavior.